Reactualization of the Contemporary Zakat Concept Kh. Sahal Mahfudh in Alleviating Poverty - Abdullah (PC Ikatan Sarjana Nahdlatul Ulama Ponorogo, 2024)
This paper analyzes about social fiqh of KH Sahal Mahfudz, there are three fundamental reasons for this research. First, KH Sahal Mahfudz is an Islamic preacher who is concerned with contemporary issues in the problem of Fiqh and Ushul Fiqh which has high sensibilities in responding to social reality developed in the Indonesian community. Secondly. He is a productive 'ulama who writes in Arabic or Indonesian. Thirdly, his historical background who lives in the NU community as well as leading Ulama in Indonesia. This paper is using a basic needs approach from contemporary Syafi'i school. This research attempts to articulate that there is a big problem in managing Zakat. This problem should be revisited to get contemporary probling solving. From this research, it could be seen that KH Sahal Mahfudz has a fundamental view that zakat today is not well managed and not well effective. He proposed the concept of zakat management through cooperation in order that the beneficiaries could be enhanced economically.